الإصابات الرضية لدى طلاب كلية التربية الرياضية بجامعة تشرين دراسة تحليلية - علي, ناظم (Latakia University Journal -Medical Sciences Series, 2017)
يعتبر البحث دراسة مسحية تهدف إلى معرفة أنواع الإصابات الرياضية لدى طلاب كلية التربية الرياضية بجامعة تشرين وأسبابها .وقد شملت الدراسة(110) مصابا من أصل)930) طالبا وهو المجتمع الكلي للدراسة. وكانت النتائج كالتالي :• الأطراف السفلية هي الأكثر إصابة وخاصة مفصلي الركبة والكاحل .• النسبة العليا من الإصابات كانت في السنوات الأولى )السنة الأولى و الثانية).• من أهم الأسباب نقص الإحماء وعدم كفاية التحضير.• نسبة الإصابات أكثر ارتفاعا في العاب القوى يليها الجمباز .The research aimed to know different kinds of sportive injuries the students of sport faculty of tishreen university have ,and the reasons behind them .The study have involved (110) scorbutics out of (930) students which is the total society of the study .The results were as follows :- The lower extremities are the most affected especially the knee and ankle joint.- The biggest percentage was in the first years ( first and second year).- The most important reasons are overheating shortage and the lack of preparation. The injures biggest rate is in athletics then comes the gymnasium .-